Assessment of myocardial deformation in patients with a singule left ventricle using CMR feature tracking and speckle tracking echcardiography. (8th February 2021) - Strodka, F; Logoteta, J; Gabbert, D; Uebing, A; Voges, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with a single ventricle are at risk for ventricular dysfunction in the long-term follow-up during and after completion of the total cavopulmonary connection (TCPC). Hence a detailed assessment of ventricular function is of high clinical relevance in those patients. Echocardiography and cardiovascular magnetic resonance (CMR) are routinely used to examine ventricular function with newer techniques, such as tissue tracking, enabling to determine regional and global myocardial deformation. Studies focusing on patients with a single left ventricle (SLV) are sparse. We assessed LV function in a larger cohort of SLV patients by using CMR feature tracking (FT) and speckle tracking echocardiography (STE). Methods: 56 SLV patients (mean age 12.0.5 ± 8.1 years) who underwent CMR as part of a routine clinical examination were included. The study population consisted of 20 patients with double inlet left ventricle (DILV), 25 patients with tricuspid atresia (TA) and 11 patients with various diagnoses. 36 patients had an echocardiographic examination within 3 months of the CMR study. Left ventricular longitudinal, circumferential and radial strain and strain rate were measured from short axis stacks at basal, midventricular and apical levels as well as from 4-chamber-views using FT. LV end-diastolic and end-systolic volumes (LVEDV, LVESV), ejection fraction (LVEF) and myocardial mass were determined from short axis images. 2D-STE was used to measure global peak systolic longitudinal strain and strain rate. In a subgroup analysis we compared patients with a DILV with patients who had TA. Results: Apart from two patients, all patients were in NYHA class I. LVEF was preserved in the total group of patients (LVEF 56.1 ± 8.4%) and correlated well with global and regional circumferential strain (r= -0.38 to -0.74, p < 0.01), global radial strain (r= 0.33, p < 0.05) and global longitudinal strain values (r= -0.31, p < 0.05). There was a mild association between LVEF and age at Fontan completion (r= -0.28, p = 0.04). There was no significant difference between the results for global longitudinal strain from FT and STE in the entire patient group. In the subgroup analysis there was no difference in LVEF, LV volumes and global strain and strain rate values from FT and STE between patients with DILV and TA. Conclusion: SLV patients in this study had a preserved ejection fraction along with an overall good health. The correlation of global and regional strain values derived from CMR FT with LVEF demonstrates that FT might be valuable to assess ventricular function in SLV patients during long-term follow-up.